Pengembangan Kampung Kelor Kelurahan Banjarsugihan Sebagai Kampung Wisata Belanja Di Kota Surabaya - Heidy Arviani; Rahma Wulandari; Ignatia Regita Wijaya; Putri Ambarwati; Rahmad Alfian Haryono (LPPM Universitas Dharma Andalas, 2022)
Banjarsugihan Village is a village located in Tandes District, Surabaya City. Banjarsugihan Village has the potential to become a moringa-based tourism village. Moringa plants in addition to having various health benefits can also improve the economy of the local community through various kinds of processed products made from moringa. Moringa village shopping tourism is one of the efforts that can be done as a forum for MSMEs, especially Moringa-based ingredients in Banjarsugihan Village to be able to improve their economy. The realization of the Moringa village shopping tour in Banjarsugihan Village has certainly gone through various stages, especially in moving back MSMEs that are no longer active in production and increasing MSME branding in Banjarsugihan Village. By observing, socializing, training to make Moringa processed products and the formation of POKDARWIS and branding of Moringa village shopping tours. Through this KKN program, it is hoped that the development of Moringa village shopping tourism in Banjarsugihan Village will make the community understand what the benefits are and how to cultivate and process Moringa into a product so that it can improve the health and welfare of the community. Through this KKN program, it is hoped that Kampung Kelor in Banjarsugihan Village, Surabaya City can become a shopping tourism village for the community